Oral Health-Related Quality of Life of Institutionalized Elderly in Serbia - Petrović, Miloš; Stančić, Ivica; Popovac, Aleksandra; Vasović, Miroslav (Vojnosanitetski pregled, 2017)
Background/Aim. Elderly residents in nursing homes have a great risk of periodontal and tooth diseases. Improving oral health can also improve residents’ general health and quality of life. The objective of our study was to investigate oral health related quality of life of institutionalized elderly in Serbia using Geriatric Oral Health Assessment Index (GOHAI). Methods. The Serbian version of the GOHAI questionnaire was developed in accordance with the recommended backward-forward method. A total of 301 participants completed the Serbian version of the GOHAI questionnaire. The questionnaire sought information about sociodemographic characteristics and self-reported perception of general and oral health. Clinical examination included assessment of periodontal and dental status. Reliability, internal consistency, and concurrent and convergent validity of GOHAI scores were examined. Results. There were 197 female and 104 male participants with the average age of 78.6 (SD ± 7.8) and average time spent in nursing home 4.9 (SD ± 4.7) years. The average score of the GOHAI was 48.4 (SD ± 8.4). Low GOHAI scores were associated with perceptions of poor oral and general health. Cronbach’s alpha coefficient for the Serbian version of GOHAI was 0.79. This instrument showed a high level of internal consistency and homogeneity between questions. The respondents who perceived that they needed dental treatment at the time had significantly lower GOHAI scores. A total of 48.5% of the participants reported ‘always’ having difficulties when chewing. On the other hand, a small number of participants (0.3%) used medications ‘always’ to relieve dental pain. Conclusion. The Serbian version of the GOHAI showed acceptable reliability and validity. The GOHAI final score was considered low, indicating low oral health self-perception by the institutionalized elderly in Serbia.